Role of Customer's Trust Moderation: E-Service Quality towards Repurchase Intention on Netflix VOD - Rissa Arvianti; Hendrati Dwi Mulyaningsih; Yudha Dwi Nughara; Dede R Oktini (Research Synergy Foundation, 2023)
This research raises issues related to the decline in Netflix users. It can be seen that customers are less interested in re-subscribing to Netflix. In fact, this is because there are several gaps that occur in the quality of the Netflix e-service. The poor quality of electronic services also has a moderate impact on the confidence of consumers who have less trust in the Netflix service. Therefore, the purpose of this study is to determine the relationship between e-service quality and repurchase intention and the role of customer trust as a moderating variable on Netflix Video-on-Demand. The method used for this research is survey method with questionnaire instrument as the data collection technique. The object of this research are 260 Netflix users that domiciled in Bandung, which was filtered into 200 users based on sampling criteria. Sampling technique in this research is using purposive sampling. There are two hypotheses in this research. To test these hypotheses, the technique used are regression analysis and MRA (Moderated Regression Analysis). The result of this research showed that there is positive and significant influence from e-service quality towards repurchase intention on Netflix Video-on-Demand. Next, customer's trust strengthens the relationship between e-service quality towards repurchase intention on Netflix Video-on-Demand.